Unusual persistence of superconductivity against high magnetic fields in the strongly-correlated iron-chalcogenide film FeTe:Ox - Dimitrov*, I.K.; Si, W.D.; Ku, W.; Han, S.J.; Jaroszynski, J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We report an unusual persistence of superconductivity against high magnetic fields in the iron-chalcogenide film FeTe:Ox below ≈ 2.5 K. Instead of saturating like a mean-field behavior with a single order parameter, the measured low-temperature upper critical field increases progressively, suggesting a large supply of superconducting states accessible via magnetic field or low-energy thermal fluctuations. We demonstrate that superconducting states of finite momenta can be realized within the conventional theory, despite its questionable applicability. Our findings reveal a fundamental characteristic of superconductivity and electronic structure in the strongly-correlated iron-based superconductors.